Synthesis, α-mannosidase inhibition studies and molecular modeling of 1,4-imino-ᴅ-lyxitols and their C-5-altered N-arylalkyl derivatives - Kalník, Martin; Šesták, Sergej; Kóňa, Juraj; Bella, Maroš; Poláková, Monika (Beilstein Journal of Organic Chemistry, 2023)
A synthesis of 1,4-imino-ᴅ-lyxitols and their N-arylalkyl derivatives altered at C-5 is reported. Their inhibitory activity and selectivity toward four GH38 α-mannosidases (two Golgi types: GMIIb from Drosophila melanogaster and AMAN-2 from Caenorhabditis elegans, and two lysosomal types: LManII from Drosophila melanogaster and JBMan from Canavalia ensiformis) were investigated. 6-Deoxy-DIM was found to be the most potent inhibitor of AMAN-2 (Ki = 0.19 μM), whose amino acid sequence and 3D structure of the active site are almost identical to the human α-mannosidase II (GMII). Although 6-deoxy-DIM was 3.5 times more potent toward AMAN-2 than DIM, their selectivity profiles were almost the same. N-Arylalkylation of 6-deoxy-DIM resulted only in a partial improvement as the selectivity was enhanced at the expense of potency. Structural and physicochemical properties of the corresponding inhibitor:enzyme complexes were analyzed by molecular modeling.
Keywords: glycosidase inhibitor; Golgi mannosidase II; iminosugar; inhibition; molecular modeling